Unmanned aerial vehicle enabled communication technologies and applications for Internet of things - Yalin LIU; Hongning DAI; Qubeijian WANG (物联网学报)
The Internet of things (IoT) is designed to provide the wide coverage and the massive connectivity service for“things” node,and the collected “things” data can provide support for the intelligent decision-making at the application layer.However,due to the fixed deployment of the access point of the “things” node,the topology of the IoT network is not flexible,consequently making it difficult to dynamically cover the IoT node or regions with high mobility.In addition,the current IoT communication technology suffers from the remote blind area,which makes it impossible for a large number of “things” node to connect to establish the “network” in some geologically-complexed regions.UAV has high mobility,low cost and flexible deployment,which is suitable to solve the above issues.Studying the communication technology of UAV assisted IoT,help the IoT to extend the existing network coverage,enhance the flexibility of the IoT topology and provide more diverse IoT service.